Tumorigenic and Differentiation Potentials of Embryonic Stem Cells Depend on TGFβ Family Signaling: Lessons from Teratocarcinoma Cells Stimulated to Differentiate with Retinoic Acid - Olga Gordeeva; Sergey Khaydukov (Stem Cells International)
A significant challenge for the development of safe pluripotent stem cell-based therapies is the incomplete in vitro differentiation of the pluripotent stem cells and the presence of residual undifferentiated cells initiating teratoma development after transplantation in recipients. To understand the mechanisms of incomplete differentiation, a comparative study of retinoic acid-induced differentiation of mouse embryonic stem (ES) and teratocarcinoma (EC) cells was conducted. The present study identified differences in proliferative activity, differentiation, and tumorigenic potentials between ES and EC cells. Higher expression of Nanog and Mvh, as well as Activin A and BMP4, was found in undifferentiated ES cells than in EC cells. However, the expression levels of Activin A and BMP4 increased more sharply in the EC cells during retinoic acid-induced differentiation. Stimulation of the Activin/Nodal and BMP signaling cascades and inhibition of the MEK/ERK and PI3K/Act signaling pathways resulted in a significant decrease in the number of Oct4-expressing ES cells and a loss of tumorigenicity, similar to retinoic acid-stimulated EC cells. Thus, this study demonstrates that a differentiation strategy that modulates prodifferentiation and antiproliferative signaling in ES cells may be effective for eliminating tumorigenic cells and may represent a valuable tool for the development of safe stem cell therapeutics.